Innovation in Nursing and Related Factors - Hamide Zengin; Öznur Tiryaki; Nursan Çınar (Association of Nurse Managers, 2020)
INTRODUCTION: Innovation plays an important role in the development and maintenance of quality in nursing care. The aim of this study was conducted of the innovation and related factors in nursing. METHODS: Before starting the study, the approval of the ethics committee and the necessary permits were obtained from the managers of the hospitals in Sakarya and Amasya. Study is made between January and February 2018, 240 volunteer nurses were included in the study. Study was used the questionnaire questioning the participants' information with 'Individual Innovation Scale'. Data were transferred to SPSS 23 package program and analyzed by number, percentage, mean, standard deviation, Kruskal Wallis and Mann Whitney U tests. The Cronbach Alpha coefficient was calculated. RESULTS: 95.8% of the participants were female, the mean age was 34.78 +- 8.48, 75% of them were married and 55% were undergraduate. 23.3% of the nurse's duty period was between 5-10 years. It was determined that 73.3% of the participants did not receive any education in the field of innovation. It was determined that 65.4% of nurses did not follow the innovative studies in the field of nursing. The total score obtained from the 'Individual Innovation Scale' was 66.62+-8.373. This situation indicates that nurses who participated in the study were "Interrogator" degree. DISCUSSION AND CONCLUSION: It was observed that the nurses who participated in the study that remained interrogative level in their studies. From the interrogative level to the innovative level; it is extremely important for nurses to be aware of what is missing or what needs to be changed, to give importance to different thoughts, to take risks, to tolerate failure (when they can not accomplish innovation), to be agile, to think freely, to view from a wide perspective.